Limiar anaeróbico de 4,0mM é capaz de estimar a máxima fase estável de lactato de jogadores de futebol em testes de campo - Barbosa Coelho, D.; Figueiredo Morandi, R.; Coelho Paixao, R.; Teixeira Mendes, T.; Alcantara Borba, D.; Lino Monteiro De-Barros, C.; Rodrigues Pereira, E.; Torres Cabido, C. E.; Silami Garcia, E. (Revista Brasileira de Ciência e Movimento, 2015)
Given the importance of aerobic capacity for the performance of soccer players, the Anaerobic Threshold has been a commonly parameter used to assess these athletes. However, there is missing information about the validity of field protocols adopted in the soccer environment. Therefore, the aim of this study was to compare the values of running speed (RS) and heart rate (HR) associated with the maximal lactate steady state (MLSS) and anaerobic threshold of 4.0mM (OBLA), and identify whether a fixed lactate concentration of 4 mM can be used to estimate the MLSS in soccer players in field tests. Twenty two soccer players of under 20 (18.1 ± 0.2 years) were evaluated. OBLA was taken as the RS corresponding to blood lactate concentration of 4.0 mM and MLSS was determined by sub maximal constant intensity exercise with a duration of 30 minutes. The results showed no significant differences between RS and HR identified by the MLSS and OBLA and showed significant correlation between the RS identified by MLSS and OBLA (r=0.56, p< 0.01). It is concluded that fixed concentration of 4 mM lactate (OBLA) can be used to estimate the RS associated with MLSS in soccer players in field tests. HR should be used with caution when applied separately for intensity control.